Histopathological Study of Oral Pseudoepitheliomatous Hyperplasia - PASCU, ROXANA MARIA (Curr Health Sci J, 2017)
ABSTRACT: Pseudoepitheliomatous hyperplasia, also called Heck’s disease, is an epithelial, inconstant and conjunctive proliferation that develops as a response to a great variety of stimuli. It is a lesion associated to different diseases, being found in the following etiopathogenic conditions: infectious pathogenic conditions, tumoral pathogenic conditions, inflammatory pathogenic conditions. We studied oral pseudoepitheliomatous hyperplasia for which we performed a histopathological study, on a group of 47 cases of oral pseudoepitheliomatous hyperplasias, where we investigated the following: oral epithelium changes, changes in the underlying lamina propria and associated etiopathogenic conditions. The main changes of the oral epithelium were: elongation of the epithelial apexes (17.02%), acanthosis (100%), dyskeratosis (14.89%), and in the underlying lamina propria: fibrosis (29.78%), inflammatory infiltrate (70.21% and vascular proliferation (10.64%). The most frequent associated etiopathogenic conditions were the infectious ones (55.31%), followed by the tumoral ones (29.79%), on the last place being the inflammatory conditions (14.89%).